(untitled) (Journal of the College of Basic Education, 2023)
The theory is an intellectual construct linked to the premises of the results. The theory builds and builds on a set ofOne of the hypotheses that in turn directs the scientific experiment and that the theory depicts it as logical principlesespecially causal and deterministic ones, and the functions of the theory differ according to the goals that directScientific law, the function of theory may be descriptive, as is the case with Kuisinck’s law.Where he emphasized that the planets revolve around the sun and their function may be explanatory if the lawsIt aims to present the causal relationships as Galilean laws that explain the phenomenon of falling bodies.